EMERGING ISSUES IN POST-BREXIT BRITAIN AND NIGERIA RELATIONS - Abraham Ejogba, ORHERO,; Henry Ejotubo, OGBE, (International Journal of Psychosocial Rehabilitation, 2024)
In recent Times, President Muhammadu Buhari and a great lot of Nigerian people, especiallyNigerians in the Diaspora alike hoped for golden times of rediscovered but deeper and partnerlike post-Brexit relations. Nigerians in diaspora considered Brexit as an opportunity for Nigeriato harness human capital development in Britain. it is open to question what UK could offerwhich other competitors such as USA, Russia, France, China and India do not have already ontheir agenda. Brexit favours economic nationalism, mercantilist doctrines of protectionism andan emphasis on national interest over international interest. It has consequences which suggest aresurgence of political realism; this is contrary to the liberal undertones of the European Union.It is against this backdrop that this paper addresses emerging issues in post-Brexit Britain andNigeria relations. The paper adopted qualitative research design as data were collected fromsecondary sources. The technique of content analysis was applied to analyze the data collectedwhich helped us to make interpretations coherently. This paper adopted the contagion effecttheory as theoretical framework of analysis. The paper concludes that Brexit decision is fraughtwith political, economic, immigration and security implications that would spread far beyond itsborders. The paper therefore recommends among others that Nigerian government shouldensure mutual interest in the post-Brexit trade relations to be negotiated and a more liberalattitude on all fronts is required to promote progressive trade partnership between Nigeria andBritain.